2017
DOI: 10.1080/0164212x.2016.1245595
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Occupational Therapy Students’ Perceptions of Spirituality in Occupational Therapy Groups: A Qualitative Study

Abstract: An exploratory-descriptive qualitative research approach explored occupational therapy students' perceptions of spirituality in occupational therapy groups during the group fieldwork process. Four focus group discussions were conducted and thematically analyzed. Four themes related to the metaphoric expressions of spirituality emerged: (1) occupational group therapy is a vehicle for spirituality; (2) spiritual journey in occupational therapy groups; (3) engaging in occupations facilitates spirituality; and (4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
2
1
0
2
Order By: Relevance
“…The educational guidelines recommend that a theory of meaning of occupational engagement and spirituality need to be part of occupational therapy education. This recommendation is consistent with previous studies, which indicated that there is a relationship between spirituality and occupational engagement (Mthembu et al, 2017b;Wilding, 2007;Wilding, May, & Muir-Cochrane, 2005).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The educational guidelines recommend that a theory of meaning of occupational engagement and spirituality need to be part of occupational therapy education. This recommendation is consistent with previous studies, which indicated that there is a relationship between spirituality and occupational engagement (Mthembu et al, 2017b;Wilding, 2007;Wilding, May, & Muir-Cochrane, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, this finding could be supported by the results of the study that reached consensus on the item "students should be aware of importance of spirituality in different fieldwork placements" (Table 2). This is supported by previous studies, which indicated spirituality plays an important role in therapy with individuals, families, groups, as well as in mental health and community (Hess & Ramugondo, 2014;Janse van Rensburg, 2014;Mthembu et al, 2017b).…”
Section: Discussionsupporting
confidence: 86%
“…These themes have been closely associated, both in occupational therapy and in psychology literature, with spirituality. In occupational therapy, spiritual occupations have been previously associated with health-promoting meaningful practices (Kang, 2003) as well as those that were life-sustaining (Mthembu et al, 2017; Wilding et al, 2005). Luboshitzky and Gaber (2001) recommended that occupational therapists address the spiritual needs of their clients by doing meaningful occupations such as holidays and family gatherings celebrations.…”
Section: Discussionmentioning
confidence: 99%
“…Por lo anterior, invitamos a quienes nos leen a explorar su espiritualidad realizando actividades tales como la meditación, el yoga, la respiración consciente, hacer arte, actividades corporales y otras formas de expresión espiritual en la vida cotidiana que contribuyan a la conexión de su ser con lo trascendental, pues posibilitan crear puentes con la naturaleza y el entorno social (Hasselkus, 2011). La práctica cotidiana de expresiones espirituales puede ayudar a estudiantes y profesionales a vislumbrar la diversidad de estas y a ampliar la noción de esta dimensión, para posteriormente incorporarlas en estrategias de valoración y atención, incluyendo la escucha activa ante los cuestionamientos existenciales (Díaz et al, 2002) y la conformación de grupos entre pares para la discusión en torno a las convicciones (Mthembu et al, 2017(Mthembu et al, , 2018. En el contexto de la atención paliativa estas discusiones se centrarían en la muerte, la vida, la espiritualidad, las prácticas religiosas, el respeto por estas y la complejidad que conlleva aplicarlas en las acciones terapéuticas (Farah y McColl, 2008).…”
Section: Encuentros Con La Ocupación Significativa Y La Espiritualidadunclassified
“…Como resultado de nuestras experiencias en la práctica, vemos importante generar espacios de reflexión y soporte emocional donde se busque el cuidado mutuo y disminuir la fatiga por compasión causada por la exposición al dolor de las personas y sus familiares. Para ello, explorar en la práctica el potencial que tiene el hacer grupal en las formas de pertenecer -tanto de estudiantes como de profesionales-en el colectivo de la Terapia Ocupacional (Mthembu et al, 2017). En consecuencia, el diálogo horizontal es vital para la configuración de un entorno seguro, de aprendizaje y de afrontamiento de desafíos (Warne y Hopes, 2009;Castillo et al, 2019).…”
Section: Desde El Diálogo Interno Hasta El Cuidado Mutuo: Fatiga Por Compasiónunclassified